The writing conundrum: A teacher’s attempt to resolve issues relating to the teaching of writing in the contemporary English classroom. - Fairbrother, Josephine (2018)
In this dissertation, I share my reflections on the complexities of teaching writing in the contemporary secondary English classroom. I consider literature which highlights that writing is rarely fully understood and that this, combined with the pressures of accountability measures and policy reforms has led to a problematic reliance on teaching decontextualized ‘skills’ rather than developing students’ ability to craft content and meaning independently. In turn I argue that this is particularly damaging for students from low socio-economic backgrounds or who are considered to be ‘low-ability’ as they are less likely to internalise these aspects in another setting. From my reading, I take the position that writing is a personal, social and contextualised act that has the potential to be incredibly powerful if taught in such a way. As such, I maintain that to not teach writing from this position is to deny students access to the powerful realms where it is a dominant form of expression and communication – reinforcing the links between the teaching of writing and social justice. To underline these claims, I collect a range of quantitative and qualitative data regarding students’ perceptions of writing and their perception of themselves as writers which demonstrate the apathy and low aspiration which occur if writing is only ever undertaken as a school-based task. I then use this to generative suggestions for alternative ways to approach the teaching of writing in a more holistic manner, as well as calling for teachers to more actively address students’ identity as writers in the classroom.